Digital Transformation in Islamic Communication: Responding to the Dynamics of Da'wah through Cybermedia - Nadia Putri Nabila; Bambang Suharto; Achmad Zaky Faiz (Jurnal Ilmiah Syi'ar, 2026)
This study aims to analyze how digital transformation through cybermedia shapes new patterns of Islamic da’wah communication in the technological era, in which the development of social media, websites, and video-based platforms creates interactive spaces that shift da’wah from a one-way communication model toward participatory communication. This research employs a literature review method by examining journals, books, conference proceedings, and scholarly documents published between 2019 and 2025 to identify trends, communication strategies, and challenges in digital da’wah.The findings indicate that the effectiveness of digital da’wah is determined by the credibility of the communicator, the design of concise and multimodal da’wah messages, and the high level of audience interactivity through features such as comments, live streaming, and digital communities. The study also identifies four main patterns of cybermedia-based da’wah interaction, namely direct responses, active participation, the formation of digital communities, and content feedback. However, digital da’wah faces serious challenges, including religious misinformation, low levels of digital literacy, and intense content competition on social media platforms.The synthesis of the literature emphasizes that the success of digital da’wah requires adaptive, dialogical, and community-based communication strategies, along with strengthened message curation and improved religious digital literacy. This study contributes by providing a comprehensive overview of the dynamics of Islamic da’wah in the cybermedia sphere and offers a theoretical foundation for developing credible, participatory, and relevant digital da’wah models that meet the needs of Muslim communities in the digital era.